Development of Poultry industry in Japan: Prospects of Guinea Fowl Production - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT Poultry products are mainly eggs and meat, both production are increasing in Japan although the number of farmers continue to decrease. This has resulted from the enlargement of the management scale. There is a necessity to find a new poultry product that could sell at a higher price for the small-scale farmers to keep retain their management In recent years, the preference of consumers have been diversified and there is a demand for many kinds of poultry products Therefore, the guinea fowl, seems to be bird that has replaced chicken in Japan. Though guinea fowl is a bird of the tropical region around West Africa, many commercial guinea fowls arc being reared in Europe. Although the guinea fowl is mainly used for meat production, they arc also excellent not only for